Rehabilitation and re-integration of women with post obstetric fistula repairs in Nigeria (2022)
Global concern exits far a holistic attention on women with Vesico-Vaginal Fistula (VVF) in lite area of rehabilitation and re-integration. This paper focused on the rehabilitation and re-integration of women with post-obstetric fistula in Nigeria. The economic and psychosocial effects of this medical condition cannot be over-emphasized. Amongst the factors accountable for its high incidence in Nigeria is traditional/cultural practices of early marriage/childbearing while the consequences include divorce, social isolation, worsening poverty, malnutrition, sexual dysfunction, mental illness (including anxiety/depression), insomnia, general ill health, and thoughts of worthlessness and suicide. To put an end to this avoidable public health pandemic; there is need for holistic consolidation of structures and safety nets for post-obstetric patients. Government should intensify policies enacted to safe-guard the girl child and woman from traditionally harmful activities. There should be engagement of social worker in the rehabilitation and re-integration of women with post-obstetric fistula